A Dyadic Approach: Applying a Developmental-Conceptual Model to Couples Coping With Chronic Illness. (April 2015) - Checton, Maria G.; Magsamen-Conrad, Kate; Venetis, Maria K.; Greene, Kathryn
The purpose of the present study was to apply Berg and Upchurch's developmental-conceptual model toward a better understanding of how couples cope with chronic illness. Specifically, a model was hypothesized in which proximal factors (relational quality), dyadic appraisal (illness interference), and dyadic coping (partner support) influence adjustment (health condition management). The study was cross-sectional and included 308 dyads in which one partner has a chronic health condition. The actor partner interdependence model shows how congruence and noncongruence in relational quality, dyadic appraisal, and dyadic coping influence dyadic adjustment.